Assortative Matching in Africa : Evidence from Rural Mozambique, Cote d'Ivoire, and Malawi - Boxho, Claire; Donald, Aletheia; Goldstein, Markus; Montalvao, Joao; Rouanet, Lea (World Bank, Washington, DC, 2019)
This paper documents novel evidence of positive assortative matching in African marriage markets along cognitive and socio-emotional skills, time and risk preferences, and education, using data from rural Mozambique, Cote d'Ivoire, and Malawi.